Capitalization of Intrajurisdictional Differences in Local Tax Prices: Comment - Dyer, James C.; Maher, Michael D. (American Economic Review, 2016)
In his recent article in this Review, Bruce Hamilton attempted to extend Peter Mieszkowski's (1969, 1972) analysis of property tax incidence. He correctly notes that Mieszkowski's model does not describe a market equilibrium. Hamilton's model accounts for the tax and benefit incidence of an intrajurisdictional property tax, and it delineates the competitive market adjustments due to capitalization effects. He then draws several conclusions regarding fundamental urban economic problems. However, Hamilton's model fails to describe a market equilibrium for the identical reason Mieszkowski's fails; potential supply adjustments generated by capitalization are neglected. The purpose of this comment is to correct the Hamilton model by including sufficient conditions to obtain a market equilibrium. Our reformulation of the model indicates that some of Hamilton's urban policy conclusions are utterly incorrect while others are valid only under very restrictive assumptions. Consider a Hamiltonian metropolitan area comprised of three jurisdictions: 1) a homogeneous high-income housing (HIH) community, 2) a homogeneous l'w-income housing (LIH) community, and 3) a mixed community consisting of a percent of units of LIH and (1 a) units of HIH. In the initial (pretax) equilibrium property values reflect only resource costs. A public service benefit is then provided equally to each house in every community. A proportional property tax is levied in each community based on the value of the average property in the jurisdiction. There are no net capitalization effects in the two homogeneous communities because the benefit per household equals the tax. However, the mixed community is characterized by short-run intrajurisdictional net benefit differentials (INBD). The LIH receive a fiscal surplus and the HIII incur fiscal burden due to average cost pricing of the public services. Hamilton concludes that the net benefit differences are capitalized into property values. Land is assumed to bear the capitalization effects because capital is mobile (p. 748, fn. 9). Hamilton defines this posttax capitalization state as (in supply of housing and public service) because land value differentials exactly reflect the present value of INBD (see pp. 748, 750, 752). For Hamilton's conclusion to hold we must assume the relative speeds of adjustment (i.e., mobility) of capital, renters, and land differ in that order, with capital exhibiting the greatest degree of mobility. This assumption is not inconsistent with Hamilton's model and is no doubt generally accepted.' It is essential to note that capitalization requires at least partial immobility of one or more factors (assuming nonzero elasticities of factor substitution).2 Furthermore, the Hamilton efficient state implies land is completely immobile and thus bears the full burden of INBD. The immobility of land eliminates substitution possibilities so an intrajurisdictional tax imposes only income effects. An